2011
DOI: 10.1007/s11524-011-9549-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Outlets, Neighborhood Characteristics, and Intimate Partner Violence: Ecological Analysis of a California City

Abstract: Neighborhood indicators of social disadvantage, such as poverty and unemployment, are associated with intimate partner violence (IPV). Despite the well-established link between heavy drinking and IPV, few studies have analyzed the contribution of alcohol outlet density to the occurrence of IPV. Greater numbers of alcohol outlets in a community may be a sign of loosened normative constraints against violence, promote problem drinking among at-risk couples, and provide environments where groups of persons at ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
112
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 30 publications
11
112
1
5
Order By: Relevance
“…This suggests that drinking prevalence, which varied markedly between countries, may have an impact on IPV that is independent of individual partner alcohol use. It is possible that the contextual effect reflects relaxed social norms and policies related to both alcohol use/availability and violence (Cunradi, 2010;Cunradi et al 2011), variable drinking culture and patterns between countries (World Health Organization, 2011), social disorganization and lack of community collective efficacy (Leslie et al 2015), and/or the density of drinking outlets, which facilitate the assembly of high-risk groups that may socially reinforce aggressive behaviors (Gruenewald, 2007). Overall, this finding supports the application of ecological models to describe the relationship between alcohol use and IPV as well as previous research that has identified an association between community-level social factors (e.g.…”
Section: Support For the Indirect And Direct Effect Modelsmentioning
confidence: 99%
“…This suggests that drinking prevalence, which varied markedly between countries, may have an impact on IPV that is independent of individual partner alcohol use. It is possible that the contextual effect reflects relaxed social norms and policies related to both alcohol use/availability and violence (Cunradi, 2010;Cunradi et al 2011), variable drinking culture and patterns between countries (World Health Organization, 2011), social disorganization and lack of community collective efficacy (Leslie et al 2015), and/or the density of drinking outlets, which facilitate the assembly of high-risk groups that may socially reinforce aggressive behaviors (Gruenewald, 2007). Overall, this finding supports the application of ecological models to describe the relationship between alcohol use and IPV as well as previous research that has identified an association between community-level social factors (e.g.…”
Section: Support For the Indirect And Direct Effect Modelsmentioning
confidence: 99%
“…Others, such as Groff (2011) expand this look at spatial density to include a look at how the presence of bars or taverns my influence spaces in close proximity. Some research looks at the influence of alcohol availability on the spatial proximity of particular crimes such as domestic violence (Cunradi, Mair, Ponicki, & Remer, 2011). Other research consolidates counts to determine concentrations or "hot spots" of liquor availability and crime (see Gorman, Li, & Horel, 2005).…”
Section: Crime and Drinking Establishmentsmentioning
confidence: 99%
“…This is changing, however, as more researchers have become aware of the advantages of Bayesian spatial models. A small but growing body of research has adopted Bayesian spatial modeling approaches in crime analysis [10][11][12][13][14][15][16][17]. For example, researchers using Bayesian spatial models have investigated contextual influences on domestic violence [12,15,18], juvenile offenders [14] and property crime [13].…”
Section: Introductionmentioning
confidence: 99%